2012
DOI: 10.1002/jbmr.1841
|View full text |Cite
|
Sign up to set email alerts
|

Primary hyperparathyroidism is associated with abnormal cortical and trabecular microstructure and reduced bone stiffness in postmenopausal women

Abstract: Typically, in the milder form of primary hyperparathyroidism (PHPT), seen in most countries now, bone density by DXA and detailed analyses of iliac crest bone biopsies by histomorphometry and µCT show detrimental effects in cortical bone, whereas the trabecular site (lumbar spine by DXA) and the trabecular compartment (by bone biopsy) appear to be relatively well preserved. Despite these findings, fracture risk at both vertebral and non-vertebral sites is increased in PHPT. Emerging technologies, such as high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
105
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(124 citation statements)
references
References 48 publications
13
105
1
5
Order By: Relevance
“…As epidemiological data have demonstrated an increased fracture risk at both vertebral and non-vertebral sites in patients with PHPT [23][24][25][26][27], newer technologies, such as HRpQCT, which measures volumetric bone density, bone geometry, skeletal microarchitecture, and bone strength in the cortical and trabecular compartments, have provided an enhanced understanding of the microstructural skeletal features in PHPT, in agreement with the fracture data. This corresponds to decreases in volumetric density in both the cortical and trabecular compartments, thinner cortices, and more widely spaced and heterogeneously distributed trabeculae [28][29][30]. These studies have also shown that the adverse effects of PHPT are likely to be mitigated by weight-bearing, since the distal radius is more affected than the tibia, a weight-bearing site.…”
Section: Asymptomatic Primary Hyperparathyroidismmentioning
confidence: 88%
See 1 more Smart Citation
“…As epidemiological data have demonstrated an increased fracture risk at both vertebral and non-vertebral sites in patients with PHPT [23][24][25][26][27], newer technologies, such as HRpQCT, which measures volumetric bone density, bone geometry, skeletal microarchitecture, and bone strength in the cortical and trabecular compartments, have provided an enhanced understanding of the microstructural skeletal features in PHPT, in agreement with the fracture data. This corresponds to decreases in volumetric density in both the cortical and trabecular compartments, thinner cortices, and more widely spaced and heterogeneously distributed trabeculae [28][29][30]. These studies have also shown that the adverse effects of PHPT are likely to be mitigated by weight-bearing, since the distal radius is more affected than the tibia, a weight-bearing site.…”
Section: Asymptomatic Primary Hyperparathyroidismmentioning
confidence: 88%
“…These studies have also shown that the adverse effects of PHPT are likely to be mitigated by weight-bearing, since the distal radius is more affected than the tibia, a weight-bearing site. Another way to evaluate the trabecular microstructure is related to trabecular segmentation analysis of the HRpQCT images, in which the trabecular network is divided into individual plates and rods [29]. Using this procedure, postmenopausal women with PHPT exhibit a trabecular network consisting of relatively fewer plate-like than rod-like trabeculae, less connectivity, and a less axially oriented trabecular network, and these are all indicative of trabecular bone deterioration in PHPT.…”
Section: Asymptomatic Primary Hyperparathyroidismmentioning
confidence: 99%
“…Although there are no animal models investigating specifically the skeletal effects of pulsatile PTH secretion, there is experimental evidence that intermittent administration of pharmacological doses of PTH has a bone anabolic effect, while continuous PTH administration is detrimental for the skeleton due to stimulation of bone resorption (9). In hyperparathyroidism is well-known the catabolic effect on skeleton by continuous exposure to PTH, bone loss can be appreciated in both cortical and trabecular compartments of the skeleton (10). Conversely, the foreshortened amino terminal peptide of PTH, teriparatide [PTH (1-34)] and the full length molecule [PTH (1-84)] are osteoanabolic when administered once daily in low doses for the treatment of osteoporosis (11)(12)(13)(14)(15).…”
Section: The Role Of Pth In Bone Remodelingmentioning
confidence: 99%
“…In particular, ITS refers to trabecular orientation and the ratio of rodlike and plate-like trabeculae, which have been recognized as important determinants of bone strength (116). Recently, the use of HR-pQCT has allowed interesting insights into the investigation of bone deterioration in secondary osteoporosis and related bone diseases (114 distribution of the trabeculae and a depletion of plate-like trabeculae, with a lower trabecular plate-to-rod ratio (117). In postmenopausal women with type 2 DM and history of fragility fractures HR-pQCT documented that both cortical bone porosity and pore volume are increased at the distal radius and distal tibia (significantly greater intracortical pore volume, relative porosity and endocortical bone surface at the ultra-distal and distal tibia; 4.7-fold greater cortical porosity at the distal radius; higher intra-cortical pore volume and larger trabecular heterogeneity at the ultradistal radius) (118).…”
Section: Ct In Osteoporosismentioning
confidence: 99%